Development of glycan-targeted nanoparticles as a novel therapeutic opportunity for gastric cancer treatment - Sofia Nascimento dos Santos; Dino Seigo Gushiken Junior; Jhonatas Pedrosa Marim Pereira; Natália Miranda Iadocicco; André Henrique Silva; Tatielle do Nascimento; Luís Alberto Pereira Dias; Flávia Rodrigues de Oliveira Silva; Eduardo Ricci-Junior; Ralph Santos-Oliveira; Emerson Soares Bernardes (Cancer Nanotechnology, 2023)
Abstract Chemotherapy resistance remains a major cause of therapeutic failure in gastric cancer. The combination of genetic material such as interference RNAs (iRNAs) to silence cancer-associated genes with chemotherapeutics has become a novel approach for cancer treatment. However, finding the right target genes and developing non-toxic, highly selective nanocarrier systems remains a challenge. Here we developed a novel sialyl-Tn-targeted polylactic acid—didodecyldimethylammonium bromide nanoparticle (PLA-DDAB) nanoparticles (NPs) loaded with dsRNA targeting ST6GalNac-I and/or galectin-3 genes. Using single photon emission computed tomography (SPECT), we have demonstrated that 99mtechnetium radiolabeled sialyl-Tn-targeted nanoparticles can reach the tumor site and downregulate ST6GalNAc-I and galectin-3 RNA expression levels when injected intravenously. Furthermore, using an in vivo gastric tumor model, these nanoparticles increased the effectiveness of 5-FU in reducing tumor growth. Our findings indicate that cancer-associated glycan-targeted NPs loaded with dsRNA targeting ST6GalNAc-I and/or galectin-3 in combination with standard chemotherapy, have the potential to become a novel therapeutic tool for gastric cancer.